Race, Risk, and Willingness of End-Stage Renal Disease Patients Without Hepatitis C Virus to Accept an HCV-Infected Kidney Transplant. Issue 4 (April 2018) - McCauley, Maureen; Mussell, Adam; Goldberg, David; Sawinski, Deirdre; Molina, Rodolfo N.; Tomlin, Ricarda; Doshi, Sahil D.; Abt, Peter; Bloom, Roy; Blumberg, Emily; Kulkarni, Sanjay; Esnaola, Gabriela; et al.
Abstract : Background: Despite effective antiviral treatment, hundreds of kidneys from deceased donors with hepatitis C virus (HCV) are discarded annually. Little is known about the determinants of willingness to accept HCV-infected kidneys among HCV-negative patients. Methods: At 2 centers, 189 patients undergoing initial or reevaluation for transplant made 12 hypothetical decisions about accepting HCV-infected kidneys in which we systematically varied expected HCV cure rate, allograft quality, and wait time for an uninfected kidney. Results: Only 29% of the participants would accept an HCV-infected kidney under all scenarios, whereas 53% accepted some offers and rejected others, and 18% rejected all HCV-infected kidneys. Higher cure rate (odds ratio [OR], 3.49; 95% confidence interval [CI], 2.33-5.24 for 95% vs 75% probability of HCV cure), younger donor (OR, 2.34; 95% CI, 1.91-2.88 for a 20-year-old vs a 60-year-old hypertensive donor), and longer wait for an uninfected kidney (OR, 1.43; 95% CI, 1.22-1.67 for 5 years vs 2 years) were associated with greater willingness to accept an HCV-infected kidney. Black race modified the effect of HCV cure rate, such that willingness to accept a kidney increased less for blacks versus whites as the cure rate improved. Patients older than 60 years and prior kidney recipients showed greater willingness to accept an HCV-infected organ. Conclusions: Most patients will consider an HCV-infected kidney in some situations. Future trials using HCV-infected kidneys may enhance enrollment by targeting older patients and prior transplant recipients, but centers should anticipate that black patients' acceptance of HCV-infected kidneys will be reduced compared with white patients. Abstract : With the availability of very efficient anti-hepatis C virus treatments, the authors ask 189 potential kidney recipients to answer various scenarios about acceptance of a HCV+ donor kidney. Age, race, and rank of transplantation are important factors in accepting such kidneys that are currently discarded. Supplemental digital content is available in the text.